2016
DOI: 10.1159/000452168
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin Water Channels and Hydrocephalus

Abstract: The aquaporins (AQPs) are a family of water-transporting proteins that are broadly expressed in mammalian cells. Two AQPs in the central nervous system, AQP1 and AQP4, might play a role in hydrocephalus and are thus potential drug targets. AQP1 is expressed in the ventricular-facing membrane of choroid plexus epithelial cells, where it facilitates the secretion of cerebrospinal fluid (CSF). AQP4 is expressed in astrocyte foot processes and ependymal cells lining ventricles, where it appears to facilitate the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
2
24
0
1
Order By: Relevance
“…We used immunofluorescence to examine the expression of aquaporin channels at the interface between the CP and olfactory bulbs. We validated each antibody using mouse kidney tissue (Supplementary Figure 2J-K) [50][51][52] . We first looked at the expression of aquaporin-1 (AQP1), as previous work has shown that AQP1 is expressed along the periphery of the olfactory bulb in neonatal mice 53 , and there is a high level of expression of AQP1, 3, and 5, within the nasal cavity 54 .…”
Section: Aquaporins At the Olfactory Nerve-bulb Interfacementioning
confidence: 99%
“…We used immunofluorescence to examine the expression of aquaporin channels at the interface between the CP and olfactory bulbs. We validated each antibody using mouse kidney tissue (Supplementary Figure 2J-K) [50][51][52] . We first looked at the expression of aquaporin-1 (AQP1), as previous work has shown that AQP1 is expressed along the periphery of the olfactory bulb in neonatal mice 53 , and there is a high level of expression of AQP1, 3, and 5, within the nasal cavity 54 .…”
Section: Aquaporins At the Olfactory Nerve-bulb Interfacementioning
confidence: 99%
“…Unlike the claudin-5 present in the tight junctions of the blood-brain barrier, the claudin-2 present in choroid plexus epithelial cells is ion and water permeable 62 and may represent a paracellular route for fluid movement. AQP1 is important in choroid plexus fluid secretion 64 and aquaporin inhibitors are beginning to be developed 65 .…”
Section: Ivh-induced Brain Injurymentioning
confidence: 99%
“…Moreover, ventricular hemoglobin can alter aquaporin expression in the choroid plexus 67 . Aquaporins are proteins that facilitate the passage of water through cell membranes and they are important in CSF production and circulation 64 . AQP alterations have been linked to the induction of hydrocephalus 74 .…”
Section: Ivh-induced Brain Injurymentioning
confidence: 99%
“…At least seven AQP subtypes have been identified in the rodent brain, and they are involved in several diseases featured by cerebral oedema, including hydrocephalus [2,37,45]. AQPs in the central nervous system facilitate water transport among the major brain compartments: the cerebrospinal fluid (CSF) space (including cerebral ventricles and subarachnoid space), the brain parenchyma (intracellular and extracellular space) and the intraventricular compartment [37,44,45,49]. Hydrocephalus occurs due to an abnormal accumulation of CSF, which is usually resulting from the blockage of CSF outflow in the ventricles or in the subarachnoid space over the brain [45].…”
Section: Introductionmentioning
confidence: 99%
“…AQPs in the central nervous system facilitate water transport among the major brain compartments: the cerebrospinal fluid (CSF) space (including cerebral ventricles and subarachnoid space), the brain parenchyma (intracellular and extracellular space) and the intraventricular compartment [37,44,45,49]. Hydrocephalus occurs due to an abnormal accumulation of CSF, which is usually resulting from the blockage of CSF outflow in the ventricles or in the subarachnoid space over the brain [45]. Two AQPs, AQP1 and AQP4, have been reported to play key roles in several hydrocephalus models and are thus potential drug targets [36,45].…”
Section: Introductionmentioning
confidence: 99%